Enzymatic Synthesis of Thymol Octanoate, a Promising Hybrid Molecule - Daniel Alberto Sánchez; Gabriela Marta Tonetto; María Luján Ferreira (Catalysts, 2023)
Interest in the synthesis and application of thymol esters has increased in recent years due to the numerous applications associated with its biological activities. The enzymatic synthesis of thymol octanoate by esterification of thymol and octanoic acid was explored using soluble lipases and immobilized lipase biocatalysts in solvent-free systems. Candida antarctica lipase B in its soluble form was the most active biocatalyst for this reaction. Different thymol and lipase feeding strategies were evaluated to maximize thymol octanoate production. The results suggest that there could be lipase inhibition by the ester product of the reaction. In this way, the optimal reaction condition was given using a thymol/acid molar ratio of 1:4 mol/mol. Under these conditions the conversion of thymol was close to 94% and the lipase maintained more than 90% of its initial activity after the reaction, showing the potential of the enzyme to be used in successive reaction cycles.